The link between attachment orientations and cellular aging among former prisoners of war. Issue 3 (3rd May 2020) - Ein-Dor, Tsachi; Hirschberger, Gilad; Tsur, Noga; Mikulincer, Mario; Bazak, Shira Buchris; Solomon, Zahava
ABSTRACT: Objective : Ex-prisoners of war (ex-POWs) experience prolonged distress that in some cases may influence their cellular aging (telomere length). The current research examines whether attachment orientations of ex-POWs and their spouses can explain individual differences in telomere length 40 years after the experience of captivity. Methods : Eighty-eight Israeli ex-POWs were assessed at four time points since captivity, whereas their spouses at three time points. Attachment orientations (anxiety, avoidance) were assessed in three time points and telomere length was measured at time four. Results : Findings indicated that ex-POWs' attachment avoidance was associated with shorter telomere length. In addition, spouses' attachment anxiety was associated with shorter telomere length among ex-POWs, whereas spouses' attachment avoidance was unexpectedly related to longer telomere length among ex-POWs. Conclusions : Results suggest that the effects of trauma on cellular aging are not uniform and that intrapersonal and interpersonal variables may moderate responses to trauma at the cellular level.